Thermospheric Conditions Associated With the Loss of 40 Starlink Satellites - Yongliang Zhang; Larry J. Paxton; Robert Schaefer; William H. Swartz (Space Weather)
Abstract We analyzed far ultraviolet data from Defense Meteorological Satellite Program (DMSP)/Special Sensor Ultraviolet Spectrographic Imager (SSUSI) and Thermosphere Ionosphere Mesosphere Energetics and Dynamics (TIMED)/Global Ultraviolet Imager (GUVI) and found significant changes in the thermospheric density and composition during the 3–5 February 2022 storm when 40 Starlink satellites started to re‐enter the atmosphere associated with increased neutral drag at an altitude around 210 km. The standard NRLMSISE‐00 model predicts only ∼5% increase in neutral density at 210 km. TIMED/GUVI observations showed a clear increase in the thermospheric N2/O column density ratio and an increase in the nitric oxide (NO) column density, indicating high thermospheric density, and temperature. DMSP SSUSI 130.4 nm limb data showed a clear increase in neutral density in the low latitude region (−30°–30°). On the duskside (17:32 LT), the density increase (compared to the pre‐storm density) is around 11%–18% at 210 km and around 18%–26% at 520 km. On the dawn‐side (05:19 LT), the density increase is more significant, 40%–59% at 210 km and ∼300% at 520 km. There are a few reasons for the dawn‐dusk asymmetry in the relative density increase: (a) the pre‐storm background density or heat capacity is lower on the dawn‐side than that on the duskside, (b) stronger auroral heating was observed on the dawnside based on analysis of auroral images, (c) the thermosphere density enhancement partially recovered when the disturbance co‐rotated with the Earth from dawn to dusk side due to enhanced infrared cooling by NO. Note that the neutral density increase is expected to be much higher at high latitudes where the neutral disturbances are initiated.